(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2015)
The article addresses the controversy in the courts over the tolerance limit for the harmful agent "noise" to be observed between 03/06/1997 and 11/18/2003, the period in which Decree 2.172/1997 was in force, for the purposes of granting special retirement and special counting of length of service. The Superior Court of Justice has ruled that the 90 decibel limit laid down in the repealed Decree should apply. In the opposite direction, the wording of Precedent No. 32 of the National Uniformization Panel of Federal Special Courts, in force until 09/10/2013, stated that the limit applicable to the period is 85 decibels, established in Decree No. 4,882/2003. Decisions in the federal regional courts have been conflicting. Although the specialized literature has paid little attention to the issue, the divergence has significant repercussions on the right to special retirement and the conversion of special service time. The aim of the article is to add elements to the discussion by analyzing the legal provision that establishes as a requirement for granting special retirement the insured person’s exposure to "harmful agents", a term that can be classified among those that national doctrine classifies as "indeterminate concepts".